ПРОФОРИЕНТАЦИЯ В УСЛОВИЯХ ПРОФИЛЬНОГО ШКОЛЬНОГО ОБРАЗОВАНИЯ (Experimental biology, 2015)
In article value of main training for realization of a problem of continuous formation and work of teachers of chair on its realization is discussed.
Keywords: problem of continuous